NORMATIVE JURIDICAL ANALYSIS OF THE POSITION OF GOVERNMENT REGULATION IN LIEU OF LAW (PERPPU) IN THE HIERARCHY OF STATUTORY REGULATIONS - Fitri Elfiani; Zulkifli; Nofrizal; Romadhan Lubis; Dearma Sinaga (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study offers a normative and juridical analysis of the position of Government Regulations in Lieu of Law (Perppu) within the hierarchy of statutory regulations in Indonesia. It investigates the constitutional and legal framework surrounding Perppu, particularly in light of its "emergency" and "temporary" nature, the President's authority to issue them without prior legislative consultation, and the requirement for subsequent approval by the House of Representatives (DPR). The research critically examines the consistency of Perppu with fundamental legal principles, including the rule of law, constitutional supremacy, and the separation of powers. It addresses the theoretical and practical controversies surrounding the application of Perppu, especially concerning the interpretation of "compelling urgency" and the potential for abuse of executive authority, which has become increasingly relevant given the rising frequency of Perppu issuances. The study argues for the need to clarify the legal standing of Perppu within the existing legal structure, strengthen parliamentary and judicial oversight mechanisms, and establish objective and measurable criteria for determining "compelling urgency." By doing so, it aims to ensure that Perppu remains a constitutional instrument, operating within defined boundaries, and does not undermine the legislative functions of the DPR or the principles of a democratic state governed by law. This normative review also seeks to address the legal and constitutional challenges in the practice of forming Perppu in Indonesia.